The Influence of Reactant Concentration on the Characteristics of the As-Synthesized Cryptomelane Nanoparticles Prepared using Precipitation Method and Its Catalytic Performance for the Degradation of A Dye - Awaluddin, Amir; Ilahi, Aulia Nur; Amiruddin, Erwin; Siregar, Siti Saidah; Milla, Zidna Mahira (Trends in Sciences, 2025)
The high purity of the nanostructured cryptomelane-type manganese oxide catalysts was successfully synthesized using the different ratio concentrations of KMnO4 over glucose through a co-precipitation method. The both reactants were simultaneously mixed with the ratios of KMnO4 to glucose of 0.4M/0.6M, 0.2M/0.3M, 0.08M/0.12M and 0.04M/0.06M, respectively. The average oxidation states (AOS) Mn of the products were determined using the back-titration method, whereas the crystalite size was calculated using Scherrer equation. The XRD analysis showed that while the phase structure remained unaffected by the concentration and calcination temperature, it had a notable impact on AOS of Mn, the morphology and the particle size as shown by the SEM images. The lowest concentration ratio resulted in the small particle size and the low AOS of Mn of the as-synthesized cryptomelane, which correlated with more Mn3+ concentration or oxygen defect in the as-synthesized cryptomelane. The vibrational mode Mn-O was demonstrated by the absorption bands appearing in the FTIR characterization results. The specific Mn-O vibrations of the cryptomelane were demonstrated using Raman spectroscopy. The catalytic activity of the as-synthesized catalysts was tested in its ability to degrade MB using a Fenton-like method. The results indicated that there is a strong correlation between the catalytic performance and Mn3+ concentration or oxygen defects present in the catalyst. The catalyst with the lowest concentration ratio possessing the high Mn3+ concentration or oxygen defects demonstrated better catalytic activity compared to the other as-synthesized catalysts. The optimization of the catalyst was performed by varying solution pH, H2O2 volume, catalyst mass, and initial concentration of methylene blue (MB). According to the research findings, this catalyst achieved a MB degradation rate of 97.01 ± 0.33 % after 120 min of contact time. This result was obtained under conditions of pH = 11, with 15 mL of 30 % H2O2, a catalyst mass of 50 mg and an initial MB concentration of 30 ppm. HIGHLIGHTS The influence of reactan concentration had a notable impact on average oxidation state (AOS) of Mn There is a strong correlation between the catalytic performance and Mn3+ concentration in the catalyst. The co-precipitation method produces a pure cryptomelane GRAPHICAL ABSTRACT